2008
DOI: 10.1120/jacmp.v9i2.2709
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characteristics of dual‐layer multileaf collimation for small‐field and intensity‐modulated radiation therapy applications

Abstract: The purpose of the present work was to measure the performance characteristics in the penumbra region and on the leaf‐end of an innovative dual‐layer micro multileaf collimator (DmMLC). The DmMLC consists of two orthogonal (upper and lower) layers of leaves; a standard MLC consists of one layer. The DmMLC provides unique performance characteristics in smoothing dose undulation, reducing leaf‐end transmission, and reducing MLC field dependence of the leaf stepping angle. Two standard MLCs (80‐leaf and 120‐leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
(49 reference statements)
1
34
0
Order By: Relevance
“…Each leaf of the DmMLC was controlled by a separate motor traveling at maximum speed of 20 mm/sec. The orthogonal layers of the DmMLC reduce MLC field dependence of the leaf stepping angle and provide fast beam response (24) , (25) . Both factors are important in MLC‐based beam tracking.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each leaf of the DmMLC was controlled by a separate motor traveling at maximum speed of 20 mm/sec. The orthogonal layers of the DmMLC reduce MLC field dependence of the leaf stepping angle and provide fast beam response (24) , (25) . Both factors are important in MLC‐based beam tracking.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, an MLC‐based beam tracking system, TrackBeam (Initia Ltd, Israel) has been assembled and evaluated in our clinic. TrackBeam utilizes a dual‐layer micro MLC (DmMLC) in combination with an online megavoltage (MV) portal imaging device (PID) and a gold fiducial marker implanted inside the tumor (24) , (25) . The MV PID determines the target position in real time by processing the fiducial marker projection (FMP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro‐MLC (mMLC) having a thinner projected leaf width of about 0.3 cm was introduced either as an add‐on accessory to the existing linac or in‐built in a dedicated linac for application in SRS. ( 6 9 ) However, a mMLC suffers from a maximum limited field size of about 10×10 cm2. A new high‐definition multileaf collimator (HDMLC) having thinner leaf width and yet providing relatively large field size was recently introduced to perform high‐precision radiosurgery and IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…The AccuLeaf micro multileaf-collimator (mMLC) developed by Azimuth Therapy Ltd features these extra banks, and is used here for the first time to compare conventional MLC tracking of conformal treatment apertures with two MLC banks with MLC tracking with four MLC banks. It has been demonstrated that the four-bank AccuLeaf mMLC offers increased conformality and reduced penumbra for aperture formation (Liu et al 2008), and also that it can confer advantage when sequencing 2D intensity-modulated beams for stepand-shoot intensity-modulated radiotherapy (Webb 2012), but the performance of the AccuLeaf mMLC for dynamic MLC tracking has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%